Design, fabrication, and measurement of textile‐based frequency selective surfaces. Issue 11 (16th June 2020) - Can, Sultan; Karakaya, Emrullah Uzay; Yılmaz, Asım Egemen
Abstract: In this study, textile based frequency selective surfaced designed, fabricated, and measured having both conformal dielectric and conductor layers. Designs are aimed to stop the band of interest for four different frequency bands, where electromagnetic pollution commonly occurs. The proposed designs are also fabricated and measured in an electromagnetically isolated environment. Each design has been simulated via CST Microwave Studio. The proposed designs named as S1, S2, S3, and S4 having S21 resonances at, 4.965 GHz 4.5 GHz, 4.6 GHz, and 3.78 GHz, respectively. For the forenamed samples, the bandwidth values are, 2.27 GHz, 0.25 GHz, 0.13 GHz, and 0.72 GHz. The experimental results have been compared with the simulation results and satisfactory agreement obtained.